Financial liberalization, saving mobilization and banking innovations - Tan, Edita A.
The paper provides an empirical analysis of the impact of the series of measures undertaken by the Philippine Monetary Authority for liberalizing the financial system. The paper notes that the measures were undertaken gradually over about 12 years. The staggered manner of liberalization is shown to produce poor results. Since 1994 when full liberalization took place, the financial market exhibited accelerated development: fairly rapid rise in saving mobilization, rapid growth in the physical financial infrastructure, a narrowing of the interest rate structure and the introduction of modern payment mechanism such as electronics transfer system. These are all welcome developments but they entail some risks. The paper concludes with recommendations for prudential and technical measures to minimize the risks that a rapidly growing financial market entail.